INTEGRATED MODEL OF SOLAR PV INTERCONNECTION USING PSSE SOFTWARE - Mohammad Nayeim Fazumy Mohd Tajudin; M.N.M. Hussain; M.M. Hussain, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Due to increase demand of renewable energy, the interest on the solar power plant has recently grown dramatically. However, when a huge generation of power was generating from the solar power plant to the grid interconnection, the system tends to create a stability problem since the generation is depend on varying of solar irradiance. A huge sudden drop of the irradiance will tend to interrupt the stability of the system. When there is large solar power is used it might be interrupting the stability of the PV plant. When there is system increase in penetration to the system the system may be loss its stability which can interrupt the system operation that cause by large penetration trough the PV system. This paper presents the development PV model from scratch until dynamic stability assessment in the PSSE software in order to study the stability of the generation of PV plant to the grid interconnection by developing 30 bus system in the software.